1998
DOI: 10.1002/(sici)1097-0215(19980330)76:1<55::aid-ijc10>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Transport of glutathione conjugates into secretory vesicles is mediated by the multidrug‐resistance protein 1

Abstract: Intracellular glutathione-conjugate transport was evaluated in the human small cell lung carcinoma cell line GLC 4 with low multidrug resistance protein (MRP 1 ) expression and its 300؋ doxorubicin-resistant, MRP 1 -over-expressing, GLC 4 -Adr subline. Transport of non-toxic concentrations of monochlorobimane and 5-chloro-methyl fluorescein diacetate was evaluated using fluorescence microscopy. After exposure to these compounds, fluorescence was observed especially in intracellular vesicles in GLC 4 -Adr. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Significant intracellular accumulation of MRP1, possibly in the Golgi, has also been reported in the drug-selected human small cell lung carcinoma cell line GLC4-Adr (72,511). In GLC4-Adr and H69AR cells, intracellular MRP1 colocalized with vesicles that accumulated fluorescent substrates (96,511). Similarly, exposure of cells transiently transfected with MRP1 fused to green fluorescent protein (GFP) to the fluorescent anthracycline doxorubicin resulted in accumulation of drug in vesicles bounded by membranes containing the fusion protein (401).…”
Section: Fig 6 Alignment Of the Nh 2 -Terminal And Cytoplasmic Loopmentioning
confidence: 80%
See 1 more Smart Citation
“…Significant intracellular accumulation of MRP1, possibly in the Golgi, has also been reported in the drug-selected human small cell lung carcinoma cell line GLC4-Adr (72,511). In GLC4-Adr and H69AR cells, intracellular MRP1 colocalized with vesicles that accumulated fluorescent substrates (96,511). Similarly, exposure of cells transiently transfected with MRP1 fused to green fluorescent protein (GFP) to the fluorescent anthracycline doxorubicin resulted in accumulation of drug in vesicles bounded by membranes containing the fusion protein (401).…”
Section: Fig 6 Alignment Of the Nh 2 -Terminal And Cytoplasmic Loopmentioning
confidence: 80%
“…For example, 80 -90% of MRP1 localizes to the plasma membrane in transfected HeLa and HEK293 cells (8,146,175,531) compared with only ϳ50% in multidrug resistant H69AR cells (8,72). Significant intracellular accumulation of MRP1, possibly in the Golgi, has also been reported in the drug-selected human small cell lung carcinoma cell line GLC4-Adr (72,511). In GLC4-Adr and H69AR cells, intracellular MRP1 colocalized with vesicles that accumulated fluorescent substrates (96,511).…”
Section: Fig 6 Alignment Of the Nh 2 -Terminal And Cytoplasmic Loopmentioning
confidence: 97%
“…Although the function of MRP1 is not fully understood, it has been assumed that it acts as an exporter of xenobiotic conjugates at the basolateral membranes of cells in several tissues. In addition, the cytoplasmic localization of MRP1 suggests a role of this protein in intracellular transport of compounds, such as transport into lysosomes (Van Luyn et al. , 1998; Kaufmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fact, we were puzzled by the notion that a cell would purposely direct the transport of potentially toxic molecules into the lumen of the Golgi apparatus since this organelle serves important functions in protein modification and sorting . Van Luyn and co-workers have previously suggested that MRP1 functions on secretory vesicles originating from the Golgi apparatus; however, these were shown to be rapidly released from the cell. This scenario seems more reasonable since the sequestered molecules would have little time to interact with components of the intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%